Aortic conduit aneurysm and enteric fistula formation in a post–liver transplant patient: A potential causative role for cytomegalovirus?. Issue 3 (25th April 2019) - King, Dominic; Neil, Desley; Forde, Colm; Mirza, Darius; Mergental, Hynek; Elsharkawy, Ahmed M
Abstract: Hepatic arterial aortic conduits can be used as an alternative means of revascularizing the donor liver when the native recipient hepatic artery (HA) cannot be used. Cytomegalovirus (CMV) is a common Herpesviridae infection in patients who have undergone solid organ transplants. It can be asymptomatic but may cause fever and invasive disease affecting any organ system. Here we describe the first case in the literature of an aortic conduit aneurysm and concurrent CMV viremia following liver transplantation. We speculate on a causative role for CMV in the development of the aneurysm.